(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2024)
The aim of this research is to find out how effective the General Election Commission (KPU) is in increasing voter participation in the 2020 Makassar Mayoral Election. This type of research uses qualitative methods. The data collection techniques used in this research are observation, interviews and direct documentation in the field. The informants in this research consisted of 6 people. The results of this research show that the Makassar City General Election Commission has been effective in its performance based on 3 (three) indicators of organizational effectiveness, namely: (1) achievement of objectives, existing voter participation is in accordance with the number of existing permanent voter lists (DPT) and voter participation has increased in 2020 compared to the previous regional elections; (2) integration, in terms of socialization the Makassar City KPU carries out socialization not only relying on face-to-face contact but also relying on digital platforms and the public can actively participate in the socialization carried out; (3) adaptation, the Makassar City KPU is able to adapt to changes in rules and regulations, as well as adapt to the changing environment due to the Covid-19 pandemic.